The Assessment of Information Model Adequacy, Realized at the Simulation Aid of Information Model in the Real Poli-Ergatic System - KOLOTUSHA, Volodymyr (Journal of Education, Technology and Computer Science, 2015)
The attempt of the assessment of information model adequacy, realized atthe simulation aid of information model in the real poli-ergatic system is describedin this article.The theories of fuzzy sets and linguistic variables were used. Its necessary tomention that this article is a realization oа author’s personal professional opinion.